A solution to achieve good reusability of MNPs Fe3O4-supported (S)-diphenylprolinoltrimethylsilyl ether catalysts in asymmetric Michael reactions. Issue 30 (7th March 2016) - Wu, Tao; Feng, Dandan; Xie, Bing; Ma, Xuebing
Abstract : A PVP-modified MNPs Fe3 O4 -supported Jøgensen–Hayashi catalyst to achieved good reusability with high yields and unchangeable excellent stereoselectivities in the asymmetric Michael addition of propanal to nitroalkenes. Abstract : A new supported ( S )-diphenylprolinol trimethylsilyl ether (Fe3 O4 /PVP@SiO2 /ProTMS) using polyvinylpyrrolidone (PVP)-modified MNPs Fe3 O4 as a support was prepared via one-pot surface-modification, and exhibited high yield (93–99%), excellent diastereoselectivities ( syn / anti = 81–96 : 19–4) and enantioselectivities (95–98% ee) in the asymmetric Michael addition of propanal to various nitroalkenes. TGA, XRD, IR, SEM, TEM, elemental analysis and N2 adsorption–desorption isotherm demonstrated that the adsorption of PVP onto MNPs Fe3 O4 resulted in the spectacular change in the chemical composition, surface morphology and pore structure of Fe3 O4 /PVP@SiO2 /ProTMS. The catalyst could be easily separated from the reaction by an external magnet and reused for ten times with high yields (77–99%) and unchanged excellent stereoselectivities (97–98% ee and syn / anti = 96/4) in the Michael addition for the first time.